Analysis of the Implementation of Murabahah Contracts on Gold Installment Products at Bank Syariah Indonesia : Case Study: BSI KCP Jember Balung - Riyatul Hasanah; Ari Sita Nastiti; Ibna Kamelia Fiel Afroh (Westscience Press, 2024)
The purpose of this study is to analyze the implementation of the murabahah contract on the gold installment product, and to find out whether the implementation of the murabahah contract on the gold installment product used is in accordance with PSAK 102. This study is a case study or field research (case study and field research). The results of this study are the implementation of the murabahah contract on the gold installment financing product at BSI KCP Jember Balung when customers buy gold from the bank, namely by paying in installments in advance for a period of time agreed upon by the customer and the bank and the recognition and measurement of murabahah financing at BSI are in accordance with PSAK 102, the presentation of Murabahah accounting at BSI is in accordance with PSAK 102 because it has been stated in the financial position report. The disclosure of Murabahah accounting is in accordance with PSAK 102 because in the BSI financial report, precisely in the BSI CALK, the total murabahah receivables, and the murabahah term, and the murabahah financing period have been disclosed.